2022
DOI: 10.3390/jdb10030028
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Histone Variant H2A.Z in Metazoan Development

Abstract: During the emergence and radiation of complex multicellular eukaryotes from unicellular ancestors, transcriptional systems evolved by becoming more complex to provide the basis for this morphological diversity. The way eukaryotic genomes are packaged into a highly complex structure, known as chromatin, underpins this evolution of transcriptional regulation. Chromatin structure is controlled by a variety of different epigenetic mechanisms, including the major mechanism for altering the biochemical makeup of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…In plants and higher eukaryotes, a correlation between histone marks, the histone variant H2A.Z, and gene transcription is evident [ 23 , 33 ]. In detail, H2A.Z colocalization with histone marks at H3 and their impact on the transcriptional output are already well described for histone H3 lysine 4 trimethylation (H3K4me3) as well as histone H3 lysine 27 trimethylation (H3K27me3) in organisms such as the model plant A. thaliana [ 36 ], mESCs [ 34 ] or the ascomycete fungus N. crassa [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants and higher eukaryotes, a correlation between histone marks, the histone variant H2A.Z, and gene transcription is evident [ 23 , 33 ]. In detail, H2A.Z colocalization with histone marks at H3 and their impact on the transcriptional output are already well described for histone H3 lysine 4 trimethylation (H3K4me3) as well as histone H3 lysine 27 trimethylation (H3K27me3) in organisms such as the model plant A. thaliana [ 36 ], mESCs [ 34 ] or the ascomycete fungus N. crassa [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yet, the role of H2A.Z is still highly controversial and poorly understood. In most tested higher organisms H2A.Z is essential, except in S. cerevisiae , Schizosaccharomyces pombe , and Neurospora crassa [ 23 25 ] already implying fundamentally pivotal roles for the histone variant H2A.Z. In general, the incorporation of H2A.Z in the nucleosome structure is associated with manifold gene regulatory functions such as gene expression, DNA repair, chromosome stability, epigenetic memory, or cell cycle progression [ 23 , 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early developmental studies using mutant mice have demonstrated that the variant histone H2A.Z is necessary for proper chromosome segregation and for the retention of the major heterochromatin protein HP1α at the PCH [ 23 25 ]. H2A.Z is present at both centric and PCH and contributes to centromere identity by maintaining optimal CENP-A levels at the centromere of mitotic chromosomes [ 25 , 26 ]. At centric heterochromatin, H2A.Z nucleosomes paired with dimethylated H3K4 are interspersed between CENP-A subdomains, while at the PCH, H2A.Z nucleosomes are paired with trimethylated H3K4 histones [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The histone variant H2A.Z is highly conserved across organisms and is essential for early embryogenesis in numerous animals 5,6 . H2A.Z histones are deposited primarily at gene regulatory regions within the genome, including at promoters surrounding the transcription start site (TSS) and enhancers 7,8 .…”
Section: Introductionmentioning
confidence: 99%